Leadership styles of bank managers in Iloilo City - Moralba, Ariel R.; Magno, Donna P.; Somcio, Suzette H.; Suede, Eduardo L.; Sumaylo, Ma. Arni B.
This research paper abridgedly tackled the dominant and backup leadership styles of bank mnagers in Iloilo City as well as the factors which affect the way they lead. It is focused on the self-perception side of leadership of thirty-three (33) respondents. It aimed to identify the common dominant and backup leadership styles of bank managers and to determine how the different factors related to managers, their subordinates, and situations influence their leadership style. The study assumed that bank managers are also leaders and they have dominant and backup leadership styles. It was found out that bank managers in the city commonly have 9,9 leadership style as their dominant style and 9,1 style as their backup leadership style. They have high concern for both production and people. If this style does not work, they lower their concern for their employees and maintain their high concern for production. It was further found out that the findings in the pattern of leadership styles of bank managers are different from that of Hodgetts (1987). It came out that the mental health and professional competence of bank managers as well as the work ethics and professionalism of their subordinates greatly affect their leadership style. Situationally, the image of the banks intensely influences the way bank managers lead. It is recommended that further research on the subordinate-perception of leadership of bank managers will be conducted since this study only revolved around the self-perception side of leadership.